(An Analysis of the Content of the Holy Qur’an and Islamic Education For The Second intermediate According to the Skills of Imaginative Thinking (Islamic Sciences Journal, 2023)
This current paper analyzes the book of the Holy Quran and Islamic Education for the second intermediate, according to their performance of the imaginative thinking skills (2021-2022) by answering the following question:What are the  imaginative thinking skills included in the content of the Holy Qur’an and Islamic education book for the second intermediate grade and the transactions of the Ministry of Education / General Directorate of Curricula in the academic year (2021-2022 )? For the purpose of the research objective, the researcher relied on the educational literature related to the topic of the research and previous studies in imaginative thinking skills in order to prepare a list that includes (3) sub-skills, (11) sub-skills, and (28) an indicator that pertains to all skills.  The researcher used the descriptive analytical method for its appropriateness to the objectives of the research. He used the book of the Holy Qur’an and Islamic Education for the second grade average for his research and used it as a sample, which was approved for the academic year (2021-2022 AD), then the researcher analyzed this textbook, and relied on the (explicit and implicit) curriculum.  The validity of the analysis is achieved using a random sample of the group of jury members. Reliability is achieved by agreement with external jury members after a period of analysis using ‘Cooper’ formula. The researcher was reached in achieving the book of the Noble Qur’an and Islamic Education for the second grade, an average of (668) recurrences and at a rate of (20%), for all results the researcher recommended the following:  Imaginative thinking skills section in the book of the Noble Qur’an and Islamic Education for the second intermediate grade is selected.  The researcher has suggested, analyzing the Holy Qur’an and Islamic education book for different stages, and teaching areas according to imaginative thinking skills.
Keywords: Content analysis, imaginative thinking skills, Cooper's equation, the Holy Quran and Islamic education, educational literature.